1999
DOI: 10.1016/s0092-8674(00)80067-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomization of Left–Right Asymmetry due to Loss of Nodal Cilia Generating Leftward Flow of Extraembryonic Fluid in Mice Lacking KIF3B Motor Protein

Abstract: In this paper (Cell 95[6], 829-837), we described the direction of the nodal cilia rotation as counterclockwise (Figure 6B). However, our recent analyses with higher spatiotemporal resolution revealed that the actual direction is clockwise when seen from the ventral side (above the nodal pit cells). In our previous observation with lower temporal resolution (10 frames per second), the direction of the rapid rotation ‫01ف(‬ rounds per second) of the nodal cilia was misinterpreted due to the artifact caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
551
1
6

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(574 citation statements)
references
References 0 publications
15
551
1
6
Order By: Relevance
“…Cilia-driven fluid flow in the mouse was originally described as "nodalflow," implying that it occurred at the embryonic organizer, the equivalent of Hensen's node (Nonaka et al, 1998). Our previous morphological and histological analysis has demonstrated that the structure in question, the distal indentation of the E7.5 mouse egg cylinder, in fact represents the posterior portion of the notochordal plate (PNC), and that the organizer itself, recognized by gene expression patterns and tissue organization, resides at the anterior end of the primitive streak but caudal to the PNC (Blum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cilia-driven fluid flow in the mouse was originally described as "nodalflow," implying that it occurred at the embryonic organizer, the equivalent of Hensen's node (Nonaka et al, 1998). Our previous morphological and histological analysis has demonstrated that the structure in question, the distal indentation of the E7.5 mouse egg cylinder, in fact represents the posterior portion of the notochordal plate (PNC), and that the organizer itself, recognized by gene expression patterns and tissue organization, resides at the anterior end of the primitive streak but caudal to the PNC (Blum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, exceptions, the most prominent example being the monocilia on the ventral cells of the distal indentation of the E7.5 mouse egg cylinder commonly referred to as the "node" (Sulik et al, 1994;Nonaka et al, 1998Nonaka et al, , 2005Marshall and Nonaka, 2006). We have previously shown that this bilaminar epithelium does not correspond to the organizer or Hensen's node (Blum et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This flow is thought to cause a build up of Nodal on the left side of the node, which is then transferred to the lateral plate mesoderm (LPM) where it sets off a cascade of signaling on the left side of the developing embryo that is maintained by a midline barrier (Nonaka et al, 1998(Nonaka et al, , 2002. While this theory of nodal flow has been widely accepted and modified to include means for both chemical (Nonaka et al, 1998;Okada et al, 2005) and physical (McGrath et al, 2003) modes of generating a left-specific signaling event, other theories have been pre-sented, including a prolonged and stable up-regulation of Ca 2ϩ in the left side of the node, which has been proposed to be involved in regulating the left-sided signaling cascade (McGrath et al, 2003;Tanaka et al, 2005). Mice lacking the membrane cation channel Polycystin-2 (PKD2) have impaired left-right axis determination and do not show left-sided elevation of Ca 2ϩ in the node (Pennekamp et al, 2002;McGrath et al, 2003).…”
Section: Introductionmentioning
confidence: 99%